Treatment outcomes 12 months after antiretroviral therapy initiation in Oman: a nationwide study from the Middle East. Issue 1 (2nd January 2023) - Elgalib, A; Shah, S.; Al-Wahaibi, A.; Al-Habsi, Z.; Al-Fouri, M.; Lau, R.; Al-Kindi, H.; Al-Rawahi, B.; Al-Abri, S.
ABSTRACT : We used routinely collected programme data on people living with HIV in Oman who started ART in 2014–2018 to assess retention on ART, viral suppression, attrition (mortality or loss to follow-up [LTFU]) and treatment failure (attrition or HIV viral load of > 1000 copies/mL) 12 months after antiretroviral therapy (ART) initiation. We identified 726 patients; 72% were male. Overall, 12 months retention on ART and viral suppression (intention-to-treat [ITT] analysis) were 85.7% and 74.5%, respectively. Attrition occurred in 14.3% (mortality of 7% and LTFU of 7.3%). Retention increased from 78.8% (93/118) to 90.6% (144/159) among patients who started ART in 2014 and 2018, respectively. Similarly, ITT and on-treatment analyses revealed that viral suppression 12 months after ART initiation increased from 57.6% (68/118) and 73.1% (68/93) among patients who initiated therapy in 2014–80.5% (128/159) and 88.8% (128/144) among patients started treatment in 2018, respectively. On multivariate analysis, older age, having "Other" as an HIV risk factor (compared to heterosexual) and receiving HIV care outside the capital Muscat independently predicted both attrition and treatment failure. Our findings have been useful in identifying factors at the individual and programme level that influenced the risk of attrition and treatment failure.